Prolonging the postharvest life of fresh mangoes with a combination of edible coatings - Nutrada Sae tang; Anthony Keith Thompson; Tongchai Puttongsiri (My University, 2020)
The effects of edible coatings to the surface of mangoes on delaying their deterioration and their quality when ripe were to investigate. Response surface methodology (RSM) was used for optimisation of the formulation of the coating. The mango cultivar selected was 'Nam Dok Mai Si Thong' and the three compounds used, were chitosan applied within the range of 0.5% to 1.5%, gum arabic applied within the range of 0% to 1.5% and rice bran oil applied within the range of 0% to 1.5%. The method proved successful with a desirability factor for weight loss, peel colour, total soluble solids: titratable acidity (TSS:TA) ratio and ripening index, during storage, always in excess of 0.99 and a composite desirability factor of 0.992. It was concluded the optimum formulation for coating mangoes for short-term storage at Thai ambient temperatures was a combination of 1.5% chitosan, 1% gum arabic and 1% rice bran oil.
Keywords: Titratable acid; Gum arabic; Rice bran oil; Nanocomposite Films for Food Packaging